Acoustic valley edge states in a graphene-like resonator system - Yang, Yahui (2019)
The concept of valley physics, as inspired by the recent development in valleytronic materials, has been extended to acoustic crystals for manipulation of air-borne sound. Many valleytronic materials follow the model of a gapped graphene. Yet the previously demonstrated valley acoustic crystal adopted a mirror-symmetry-breaking mechanism, lacking a direct counterpart in condensed matter systems. In this paper, we investigate a two-dimensional (2D) periodic acoustic resonator system with inversion symmetry breaking, as an analogue of a gapped graphene monolayer. It demonstrates the quantum valley Hall topological phase for sound waves. Similar to a gapped graphene, gapless topological valley edge states can be found at a zigzag domain wall separating different domains with opposite valley Chern numbers, while an armchair domain wall hosts no gapless edge states. Our study offers a route to simulate novel valley phenomena predicted in gapped graphene and other 2D materials with classical acoustic waves.